L’ennemi dans l’après-guerre espagnole, 1939-1945 - Javier Domínguez Arribas (Cahiers de Civilisation Espagnole Contemporaine)
This paper studies the figures of the enemy at the beginning of the Spanish postwar period (1939-1945), as they were depicted by the rising Franco regime. Leftists, separatists, Freemasons, and Jews are taken into consideration, and particular attention is paid to the disproportion between the levels of both repression and rhetoric, regarding the persecution they suffered and the discourse that stigmatized them. Surprisingly, the enemies that were actually hit by the bloodiest repression –the “reds”– were not always those who received the worst attacks in propaganda. Finally, an interpretation of the functions played by the enemy’s representation within the Francoist system is proposed.